Exploration and commitment in precarious contexts. Construction of psychosocial identity in adolescents from four schools in the city of Lima - Pease Dreibelbis, Maria Angelica (2025)
Constructing a psychosocial identity is the key task during adolescence and, according to Erikson’s theory, it is achieved through exploration in different domains which leads to subsequent commitments. Cross-cultural evidence, however, shows that this process is not the same around the world. In this study, based upon interviews administrated to 20 adolescents from 4 different schools of Lima, the capital city of Peru, we investigated variations in psychosocial identity construction processes and the way adolescents understood this process. Results reveal contextual variations regarding the possibility of exploring various options before committing to an occupation, and difficulties constructing values and ideas different from their parents which results in different ways to approach the experience of being adolescents. In the friendship and dating domains, although there are contextual variations, there are more common aspects. These results attempt to contribute to gaining a deeper understanding of adolescent development in culturally diverse contexts such as Peru.